2010
DOI: 10.1143/jpsj.79.063001
|View full text |Cite
|
Sign up to set email alerts
|

Brownian Dynamics around the Core of Self-Gravitating Systems

Abstract: We derive the non-Maxwellian distribution of self-gravitating N-body systems around the core by a model based on the random process with the additive and the multiplicative noise. The number density can be obtained through the steady state solution of the Fokker-Planck equation corresponding to the random process. We exhibit that the number density becomes equal to that of the King model around the core by adjusting the friction coefficient and the intensity of the multiplicative noise. We also show that our m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
3
8
0
Order By: Relevance
“…Here, note that we have reported similar results in our previous letter [11]. In this paper, however, we demonstrate how we executed our numerical simulations.…”
supporting
confidence: 83%
“…Here, note that we have reported similar results in our previous letter [11]. In this paper, however, we demonstrate how we executed our numerical simulations.…”
supporting
confidence: 83%
“…(1) with κ ∼ 3/2 [4][5][6]. Furthermore, we have reported that the same density profile is obtained through N-body simulations of 3DSGS [2,3]. Therefore, we can conclude that the SGSs without boundary have the universal density profile depicted by Eq.…”
Section: Fokker-planck Modelsupporting
confidence: 67%
“…QES of Hamiltonian mean field model which is a toy model of systems with long range interactions varies from a ferromagnetic state to a paramagnetic (homogeneous) state with increase of the initial total energy [1]. We have obtained numerically the result that the number density N of three dimensional self-gravitating system (3DSGS) in the real space can be approximated by the following representation when the initial virial ratio V (≡ 2K/Ω) is 0 where K and Ω are the total kinetic and gravitational energy respectively [2,3]:…”
Section: Introductionmentioning
confidence: 99%
“…
We investigate the quasi-equilibrium state of one-dimensional self-gravitating systems. If the null virial condition is satisfied at initial time, it is found that the number density around the center of the system at the quasi-equilibrium state has the universality similar to two-and three-dimensional self-gravitating systems reported in [1,2]. The reason why the null virial condition is sufficient for the universality is unveiled by the envelope equation.
…”
mentioning
confidence: 80%
“…QES of Hamiltonian mean field model which is a toy model of systems with long range interactions varies from a ferromagnetic state to a paramagnetic (homogeneous) state with increase of the initial total energy [1]. We have obtained numerically the result that the number density N of three dimensional self-gravitating system (3DSGS) in the real space can be approximated by the following representation when the initial virial ratio V (≡ 2K/Ω) is 0 where K and Ω are the total kinetic and gravitational energy respectively [2,3]:…”
Section: Introductionmentioning
confidence: 99%